What do EFL Teachers Seek in Professional Development Programs? Voices from Teachers (2002)
ABSTRACT: This article reports the findings of a qualitative study about the needs reported by EFL (English Foreign Language) teachers in their professional work, carried out in Medellín, Colombia. Two groups of public school teachers and two of private school teachers participated in the data collection. Focus group sessions and a questionnaire were used as data collection instruments. Results suggest that EFL teachers experience needs in three different domains of their professional lives: as workers, as instructors, and as learners. Traditional approaches have overestimated their role as instructors denying the importance of the other two domains. The authors conclude that EFL teachers look for professional development programs that address the three domains holistically. They call for teacher educators’ attention to explore possibilities to fulfill those needs